KONSEP PEMIKIRAN ATH-THUFI TENTANG MASHLAHAH SEBAGAI METODE ISTINBATH HUKUM ISLAM - Imam Fawaid (LP2M Universitas Ibrahimy, 2014)
Najmuddin ath-Thufi is a scholar of fiqh and usulfiqh, born in Thufi Baghdat Iraq. He was a scientist, he studied fiqh, ushulfiqh, Arabic, manthiq, theology, hadith, tafsir, history, and jadal. Ath-Thufi is one of Islamic law philosophy, his theori is adabtabilitas, it’s rule that Islamic law as the law created by God, and can adapt to the times. So, it can be changed in order to realize the benefit of mankind. The framework is the principle Maslahah adaptability. Maslahah principle as a fundamental value for the sustainability of Islamic law in the context of social change, which is able to respond to any social change. This study to determine about al-Thufi theory, maslahah as istinbath Islamic law.